Mitophagy promotes sorafenib resistance through hypoxia-inducible ATAD3A dependent Axis - Hong Wu; Tao Wang; Yiqiang Liu; Xin Li; Senlin Xu; Changtao Wu; Hongbo Zou; Mianfu Cao; Guoxiang Jin; Jinyi Lang; Bin Wang; Baohua Liu; et al. (Journal of Experimental & Clinical Cancer Research, 2020)
Abstract Background The identification of novel targets for recovering sorafenib resistance is pivotal for Hepatocellular carcinoma (HCC) patients. Mitophagy is the programmed degradation of mitochondria, and is likely involved in drug resistance of cancer cells. Here, we identified hyperactivated mitophagy is essential for sorafenib resistance, and the mitophagy core regulator gene ATAD3A (ATPase family AAA domain containing 3A) was down regulated in hypoxia induced resistant HCC cells. Blocking mitophagy may restore the sorafenib sensitivity of these cells and provide a new treatment strategy for HCC patients. Methods Hypoxia induced sorafenib resistant cancer cells were established by culturing under 1% O2 with increasing drug treatment. RNA sequencing was conducted in transfecting LM3 cells with sh-ATAD3A lentivirus. Subsequent mechanistic studies were performed in HCC cell lines by manipulating ATAD3A expression isogenically where we evaluated drug sensitivity, molecular signaling events. In vivo study, we investigated the combined treatment effect of sorafenib and miR-210-5P antagomir. Results We found a hyperactivated mitophagy regulating by ATAD3A-PINK1/PARKIN axis in hypoxia induced sorafenib resistant HCC cells. Gain- and loss- of ATAD3A were related to hypoxia-induced mitophagy and sorafenib resistance. In addition, ATAD3A is a functional target of miR-210-5p and its oncogenic functions are likely mediated by increased miR-210-5P expression. miR-210-5P was upregulated under hypoxia and participated in regulating sorafenib resistance. In vivo xenograft assay showed that miR-210-5P antagomir combined with sorafenib abrogated the tumorigenic effect of ATAD3A down-regulation in mice. Conclusions Loss of ATAD3A hyperactivates mitophagy which is a core event in hypoxia induced sorafenib resistance in HCC cells. Targeting miR-210-5P-ATAD3A axis is a novel therapeutic target for sorafenib-resistant HCC.